BAHAN BACAAN KEAGAMAAN AKTIVIS KAMPUS DI UNIVERSITAS PADJADJARAN (UNPAD) BANDUNG: THE CAMPUS ACTIVISTS’RELIGIOUS READING MATERIALS AT PADJADJARAN UNIVERSITY (UNPAD) BANDUNG - Mahmudah Nur (Penamas, 2016)
This research presented the research results of the campus activists’ Islamic readings at Padjadjaran University (UNPAD) Bandung. In particular, the active students who became a member and commite of the students’ religious organization at UNPAD campus.This was a qualitative research with descriptive-analysis design to describe Islamic activists’ reading materials at UNPAD. This research used the opened interview and literature study in collecting data. The data were analyzed based on the field data as the results of opened interview and literature study. The content analysis were used to analyze the content of campus activists’ reading namely the title, author, subject matter, and language categories. Whereas, the discourse analysis were used to analyze the substance of research literatures. All literatures would be identified, be inventoried, and be analyzed to know its characteristics, tendencies, purposes, and discourses. The results of research showed that the religious reading materials that its had been read and studied by UNPAD Islamic activists’ were many variations. Not only they used from printed resources but also from soft resources. From this writing context point of view, based on their religious reading literatures, the campus activists could be divided into three typologies. First, the activist students at university level; second, the activist students at faculty level, and third, the activist students at religious external organization. Keywords: Religious reading, campus activist, reading behavior, student Tulisan ini menyajikan hasil penelitian mengenai bacaan keagamaan aktivis kampus di Universitas Padjadjaran Bandung, Khususnya mahasiswa yang aktif, baik sebagai anggota maupun pengurus dalam organisasi keagamaan di kampus UNPAD. Penelitian ini merupakan studi kualitatif dengan rancangan deskriptif- analitis, yang ingin mendeskripsikan bahan bacaan aktivis keagamaan Islam di kampus UNPAD. Teknik pengumpulan data menggunakan metode wawancara terbuka dan studi pustaka. Analisis data dilakukan berdasarkan bahan-bahan dari lapangan, berupa hasil wawancara terbuka dan studi pustaka. Analisis isi digunakan untuk menganalisis ‘isi’ literatur bacaan aktivis kampus, yaitu: judul, pengarang, bidang kajian, dan kategori bahasanya. Sedangkan analisis wacana digunakan untuk menganalisis substansi literatur kajian. Literatur-literatur yang ada diidentifikasi, diinventarisasi, dan dianalisis untuk mengetahui karakteristik, kecenderungan, arah, dan wacananya. Penelitian ini menunjukkan, bahwa bahan bacaan keagamaan yang dibaca dan dikaji oleh aktivis keagamaan Islam UNPAD, baik dilihat dari tema maupun perilakunya sangat bervariasi, selain mengandalkan sumber cetak juga menggunakan sumber Jaringan Internet (daring). Di samping itu, aktivis kampus dalam konteks tulisan ini dilihat dari literatur bacaan keagamaan terbagi menjadi 3 (tiga) tipologi, yaitu: pertama, mahasiswa yang aktif di tingkat universitas; kedua, mahasiswa yang aktif di tingkat fakultas, dan ketiga, mahasiswa yang aktif di tingkat organisasi lembaga eksternal keagamaan. Kata Kunci: Bacaan keagamaan, aktivis kampus, perilaku membaca, mahasiswa